Helicobacter pylori upregulates matrilysin (MMP-7) in epithelial cells in vivo and in vitro in a Cag dependent manner. Issue 10 (11th September 2003) - Bebb, J R; Letley, D P; Thomas, R J; Aviles, F; Collins, H M; Watson, S A; Hand, N M; Zaitoun, A; Atherton, J C
Abstract : Background and aims: Matrix metalloproteinase-7 (MMP-7) is important in normal and pathological remodelling of epithelial-matrix interactions, and is upregulated in gastric cancer. Helicobacter pylori infection is the first stage in gastric carcinogenesis, and therefore our aim was to determine if H pylori upregulated gastric MMP-7 expression and if this was affected by strain virulence. Methods: We took gastric biopsy specimens at endoscopy from H pylori infected (n = 17) and uninfected (n = 18) patients and assessed MMP-7 expression by ELISA, real time polymerase chain reaction (PCR), and immunohistochemistry (concentrating on epithelial cells in the proliferative zone). We PCR typed H pylori for cagE and vacA . We performed H pylori /cell line coculture studies with wild-type pathogenic and non-pathogenic H pylori strains and with CagE − and VacA − isogenic mutants. Results: Gastric biopsy specimens from H pylori + patients expressed higher levels of MMP-7 at the protein and mRNA levels in the antrum and corpus (for example, by ELISA: H pylori + 0.182 OD units v H pylori − 0.059; p = 0.009 antrum). Epithelial cells from H pylori+ patients stained more intensely for MMP-7 than those from uninfected patients, including in the proliferative zone containing pluripotent cells (p<0.03 antrum, p<0.04 body). Upregulation of MMP-7 in epithelial cells was confirmed at the protein and mRNA levels by H pylori /cell line coculture. These experiments also showed that MMP-7 upregulation was dependent on an intact H pylori cag pathogenicity island but not on the vacuolating cytotoxin. Conclusion: We speculate that increased expression of MMP-7 in H pylori gastritis may contribute to gastric carcinogenesis.